The dark side of democratization: dysfunctional democracies in south america? - Laurence Whitehead (Universidad de Los Andes, 2003)
This article analyzes the apparently dysfunctional democracies that have become common in Latin America. Although democratic in the conventional sense that national leadership is periodically contested and renewed through standardized electoral procedures, such regimes also exhibit systematic political dysfunctionality. The author evaluates experiences with democracy in Argentina, Colombia, and Venezuela in order to illustrate this concept, and examines their comparative and theoretical implications